Initial validation of the Spanish Childhood Trauma Questionnaire-short form: Factor structure, reliability and association with parenting - Arntz, Arnoud (Journal of interpersonal violence, 2013)
The present study examines the internal consistency and factor structure of the Spanish version of the Childhood Trauma Questionnaire-Short Form (CTQ-SF) and the association between the CTQ-SF subscales and parenting style. Cronbach's α and confirmatory factor analyses (CFA) were performed in a female clinical sample (n = 185). Kendall's ι correlations were calculated between the maltreatment and parenting scales in a subsample of 109 patients. The Spanish CTQ-SF showed adequate psychometric properties and a good fit of the 5-factor structure. The neglect and abuse scales were negatively associated with parental care and positively associated with overprotection scales. The results of this study provide initial support for the reliability and validity of the Spanish CTQ-SF